How Accessible the University Websites in Indonesia for People with Disabilities? - Fitri Dwi Arini (Indonesian Journal of Disability Studies, 2020)
Website in higher education utilized for many purposes such as providing learning resources, information, and news related to student's academic needs. For this purpose, university websites must be accessible for all users including students with disabilities. This article describes a study conducted to evaluate the accessibility of university websites for people with disabilities in Indonesia. The accessibility evaluation focused on compliance with the most recent international standards provides by The World Wide Web Consortium (W3C) called WCAG 2.0. A quantitative research would be utilized in this study using website accessibility online evaluation tools namely, Achecker. This study comprises the analysis of accessibility of 20 websites from top-ranked universities in Indonesia based on webometrics ranking. The result of this study showed that 95% of the university websites examined carried problems in conformity with WCAG 2.0 Level AAA.